Correlation of Venusian Mesoscale Cloud Morphology Between Images Acquired at Various Wavelengths. Issue 6 (9th June 2022) - Narita, M.; Imamura, T.; Lee, Y. J.; Watanabe, S.; Yamazaki, A.; Satoh, T.; Taguchi, M.; Sato, T. M.; Fukuhara, T.; Yamada, M.; Kouyama, T.; Iwagami, N.
Abstract: The differences and similarities in morphologies acquired across various wavelengths in simultaneously obtained Venus' dayside images may provide clues on cloud/atmospheric physics and chemistry. Here, we focus on spatial scales smaller than ∼600 km, where cell‐like or streaky features seem to dominate in ultraviolet images. Using images acquired at ultraviolet wavelengths of 283 nm, 365 nm, and infrared wavelengths of 0.90, 2.02, and 10 μm by the Venus orbiter Akatsuki, correlation coefficient maps between pairs of wavelengths, such as 2.02 μm/10 μm, 2.02 μm/283 nm, 2.02 μm/365 nm, 283 nm/365 nm, and 0.90 μm/2.02 μm were created. Our results show a clear negative correlation between images obtained at 2.02 μm (CO2 absorption) and 10 μm (cloud top temperature), meaning that elevated clouds are cooled by adiabatic expansion or the ambient air. A clear negative correlation was found between 2.02 μm and 283 nm (SO2 absorption), suggesting that SO2 is transported to the cloud top region during cloud ascent. We observed a clear positive correlation between images obtained at 283 and 365 nm (unknown absorber), implying a close relationship between the unknown absorber and SO2 or a non‐negligible contribution of the unknown absorber at 283 nm. We found a low correlation between images obtained at 0.90 μm (middle/lower cloud) and 2.02 μm, suggesting a weak vertical coupling in the clouds. Plain Language Summary: Sulfuric acid clouds cover the whole globe of Venus at altitudes of 50–70 km. These clouds show various patterns at ultraviolet and infrared wavelengths. The physical/chemical processes that create the cloud patterns are not fully known. Atmospheric variables such as cloud height and temperature can be mapped at various wavelengths. The relationship between the spatial patterns at these wavelengths provides crucial information on the processes that create such cloud features. We used image data obtained at multiple wavelengths by the Venus orbiter Akatsuki to investigate the correlation of small‐scale (<600 km) cloud patterns acquired at various wavelengths, namely 283 nm (SO2 abundance), 365 nm (the unknown absorber), 0.9 μm (middle/lower cloud), 2.02 μm (cloud top altitude), and 10 μm (cloud top temperature). The correlations among these wavelengths place new constraints on the processes responsible for the cloud production. For example, a negative correlation was found between 2.02 μm and 283 nm, suggesting that SO2 is transported to the cloud top region during cloud ascent. Key Points: We performed a statistical analysis on the correlation of small‐scale patterns on the Venus dayside acquired at various wavelengths Significant correlation was found between the ultraviolet absorption, the cloud top altitude and the cloud top temperature We propose that vertical motions in the upper cloud region play an important role in creating small‐scale patterns